Dureza del agua de consumo doméstico y prevalencia de eczema atópico en escolares de Castellón, España Domestic water hardness and prevalence of atopic eczema in Castellon (Spain) schoolchildren - Alberto Arnedo-Pena; Juan Bellido-Blasco; Joan Puig-Barbera; Adrián Artero-Civera; Joan Baptista Campos-Cruañes; Mª Rosario Pac-Sa; Jose Luis Villamarín-Vázquez; Carlos Felis-Dauder (Salud Pública de México, 2007)
OBJETIVO: Estudiar la asociación entre la prevalencia de eczema atópico (EA) y la dureza del agua de uso doméstico. MATERIAL Y MÉTODOS: El estudio ISAAC (International Study of Asthma and Allergies in Childhood) estimó la prevalencia de EA en seis localidades de Castellón, España, en escolares de 6-7 y 13-14 años durante 2002. Se establecieron tres zonas de <200 mg/l, 200-250 mg/l, y >300 mg/l según la dureza del agua doméstica de esas localidades. Se empleo regresión logística en el análisis. RESULTADOS: En escolares de 6-7 años, las prevalencias acumuladas de EA en las tres zonas fueron de 28.6, 30.5 y 36.5%. Entre la zona 1 y la zona 3, la razón de momios ajustada (RMa) fue 1.58 (IC 95% 1.04-2.39) (prueba de tendencia ajustada p=0.034). La prevalencias de síntomas de EA en el último año fueron de 4.7, 4.5, y 10.4%, respectivamente. Entre la zona 1 y la zona 3, la (RMa) fue 2.29 (IC95% 1.19-4.42) (prueba de tendencia ajustada p=0.163). En escolares de 13-14 años no se apreciaron tendencias significativas. CONCLUSIONES: Se sugiere que la dureza del agua podría tener alguna importancia en el desarrollo de la enfermedad en los escolares de 6-7 años. Water hardness has been associated with atopic eczema (AE) prevalence in two epidemiologic studies carried out on schoolchildren in England and Japan. OBJECTIVE: To estimate the association between the prevalence of AE and domestic water hardness. METHODS: The prevalence of AE was obtained from The International Study of Asthma and Allergies in Childhood, carried out in six towns in the province of Castellón on schoolchildren 6-7 and 13-14 years of age, using a standard questionnaire in 2002. Three zones were defined according to domestic water hardness of the six study localities: <200 mg/l, 200-250 mg/l, and >300 mg/l. A logistic regression analysis was performed. RESULTS: The lifetime prevalence of AE in schoolchildren 6-7 years of age was higher with the increment of water hardness, 28.6, 30.5 and 36.5% respectively for each zone; between zone 1 and zone 3, the adjusted odds ratios (ORa) were 1.58 (95% Confidence Intervals [CI] 1.04-2.39) (adjusted tendency test p=0.034). Prevalence of symptoms of AE within the past year were 4.7, 4.5, and 10.4%, respectively by zone; between zone 1 and zone 3, the ORa was 2.29 (95% CI 1.19-4.42) (adjusted tendency test p=0,163). For 13-14 year-old schoolchildren, tendencies to lifetime prevalence of AE at any time or in the past year were not significant. CONCLUSIONS: This study suggests that in 6-7 year-old schoolchildren, water hardness in the area where they live has some relevance to the development of the disease.